Accessibility of urban park benefits with different spatial coverage: Spatial and social inequity. (October 2021) - Zhang, Ran; Sun, Fengyun; Shen, Yanan; Peng, Shengjing; Che, Yue
Abstract: The increasing environmental deterioration that cities face, such as heat island effects, noise and air pollution, can be mitigated by urban park benefits (UPBs). As a result, UPBs are closely related to the well-being of urban residents and are considered an important element of environmental equity. However, the spatial coverage of UPBs considered in previous studies is restricted to the location of urban parks, and the spatial transfer capability of some UPB types is largely ignored. This study divides UPBs into four categories, i.e., park entry benefits, small space benefits, medium space benefits, and size-determined benefits. We investigate the acquisition levels of these four UPB categories in Shanghai's central city by park accessibility indices, integrating spatial and social dimensions. The results show that sub-districts with higher socioeconomic status are more likely to have good access to the four UPB categories. Fortunately, elderly and unemployed individuals also have easier access to UPBs as do those with higher socio-economic status. Despite parents' desire to have parks nearby for their children's growth, inequities of access to UPBs are found among children. The research methods and results of this paper have implications for urban planning practices. Highlights: The multiple benefits offered by urban parks were classified according to their spatial coverage. Accessibility was calculated based on access to the benefits provided by urban parks rather than access to the location of urban parks. Areas lacking urban park services were identified. Children may have less access to the multiple benefits that urban parks offer than the elderly.